Digitization and digital archiving : a practical guide for librarians - Leggett, Elizabeth R., 1985- (Lanham : Rowman & Littlefield, 2014)
More and more, library patrons are embracing the ease with which information can be accessed digitally. In an instant, a few keywords can bring patrons exactly what they desire, such as a book or a photograph, rather than going through the much more tedious activity of browsing through shelves, searching for a call number, or, even more daunting, the process of trying to work a microfilm reel. Thus, many librarians in libraries of every size and type are currently working toward making more information available electronically. This process can be daunting, however.' Digitization and digital archiving: a practical guide for librarians' seeks to answer the following common questions: What should be stored? Where and how should it be stored? How exactly is information stored in a computer? Does it really make a difference if one uses a jpg or a tiff file? This book is a comprehensive guide to the process of digital storage and archiving. Assuming only basic computer knowledge, this guide walks the reader through everything he or she needs to know to start or maintain a digital archiving project. Any librarian interested in how digital information is stored can benefit from this guide.
Why use digital preservation? -- How do computers store information? -- Storing images -- Storing text -- Storing audio and video -- CDs, DVDs, and Blu-ray -- Magnetic tape -- Hard drives -- Flash memory -- Cloud computing -- Equipment for digitizing and editing archival materials -- Metadata and accessing information -- Copyright law -- Problems with digital archiving -- Putting it all together.
Includes bibliographical references and index.
Keywords: Archival materials -- Digitization; Archival materials -- Conservation and restoration; Digital preservation; Records -- Management; Electronic records -- Management; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science; Archival materials -- Conservation and restoration; Archival materials -- Digitization; Digital preservation; Electronic records -- Management; Records -- Management; Arkivmaterial; Digitalt bevarande; Elektroniska informationsresurser; Digitalisering